1816 and 2020: The Years Without Summers - Sharren, Kandice; Moffatt, Kate (Romanticism on the Net)

(untitled) (Université de Montréal, 2020)
The WPHP Monthly Mercury is the podcast for the Women’s Print History Project (WPHP), a bibliographical database that seeks to provide a comprehensive account of women’s involvement in print in a long Romantic period. The podcast provides us with an opportunity to develop in-depth analyses of our data. The December 2020 episode, “1816 and 2020: The Years Without Summers,” explores women’s writing in the WPHP inspired by 1816, known as the Year Without a Summer, when abnormally cold weather, exacerbated by the aftermath of the Napoleonic Wars, led to crop failures and typhus and cholera epidemics. Often remembered as the cold and fog-laden year in which an 18-year-old Mary Shelley came up with the idea for Frankenstein, 1816 was a year of catastrophe more generally. In this episode, hosts Kate Moffatt and Kandice Sharren explore how the bibliographical metadata contained in the WPHP can uncover a wider range of voices writing about catastrophe. Our findings, which include political writing, travel memoirs, and poetry, reveal the lived experiences of women in a tumultuous time. We conclude by meditating on the nature of literary production during catastrophe, and how our own experiences during the upheavals of 2020 influenced our approach to the books that we uncovered.